Streetwise, and : Tiny, the life of Erin Blackwell [videorecording (DVD)] . - Bell, Martin, 1943-; Bell, Martin, 1943-; Mark, Mary Ellen, 1940-2015; McCall, Cheryl; Blackwell, Erin, 1969-; Marsh, Kimberly; Waits, Tom, 1949-; Patscha, Glenn (Criterion collection, 2021)
"In 1983, director Martin Bell, photographer Mary Ellen Mark, and journalist Cheryl McCall set out to tell the stories of homeless and runaway teenagers living on the margins in Seattle. Streetwise follows an unforgettable group of kids who survive by hustling, panhandling, and dumpster diving. Its most haunting and enduring figure is iron-willed fourteen-year-old Erin Blackwell, a.k.a. Tiny; the project's follow-up, Tiny: The Life of Erin Blackwell, completed thirty years later, draws on the filmmakers' long relationship with their subject, now a mother of ten. Blackwell reflects with Mark on the journey they've experienced together, from Blackwell's battles with addiction to her regrets to her dreams for her children, even as she sees them repeat her own struggles. Taken together, the two films create a devastatingly frank, empathetic portrait of lost youth growing up far too soon in a world that has failed them, and of a family trying to break free of the cycle of trauma--as well as a summation of the life's work of Mark, an irreplaceable artistic voice"--Container.